Modified Riceberry rice extract suppresses melanogenesis-associated cell differentiation through tyrosinase-mediated MITF downregulation on B16 cells and in vivo zebrafish embryos - Rodboon, Teerapat (Res Pharm Sci, 2020)
BACKGROUND AND PURPOSE: Excessive melanin production caused by overactive tyrosinase (TYR) enzyme results in several dermatological problems. The TYR inhibitor, derived from metabolite changes during fermentation, has been well recognized for pigmentation control. EXPERIMENTAL APPROACH: This study is interested in alternative anti-melanogenic agents from bio-modified Riceberry rice through fermentation. Modified Riceberry rice extract (MRB) was evaluated for its cytotoxicity, melanin content, melanin excretion, and TYR activity in B16 cells. TYR and their melanogenesis-related molecules such as TYR-related proteins-1 and -2, and microphthalmia-associated transcription factor (MITF) were determined. The anti-melanogenic activity and toxicity were also tested using the embryonic zebrafish model. Furthermore, comprehensive genotoxicity testing was verified by cytokinesis-block micronucleus cytome assay. FINDINGS/RESULTS: The study found that non-cytotoxic concentrations of MRB at 20 and 40 mg/mL inhibited melanogenesis and melanin excretion by interfering B16 cell morphology. Cellular TYR enzymatic activity was also suppressed in the treated cells. The mRNA transcription and protein expression levels of TYR and MITF decreased by dose-dependent and time-dependent manners with MRB treatment. In the animal model, MRB was found to be safe and potent for melanogenesis-related TYR inhibition in embryonic zebrafish at 20 and 30 mg/mL. The toxicity of effective doses of MRB showed no genotoxicity and mutagenicity. CONCLUSION AND IMPLICATIONS: This study suggests that MRB has anti-melanogenesis potential through TYR and its-related protein inhibitions. MRB is also safe for applications and maybe a promising anti-melanogenic agent for hyperpigmentation control.